Charles Bonnet Syndrome: A Precursor To Alzheimer Disease - Janaki V.,; Rosdinom R.,; Hatta S., (Penerbit UKM, 2015)
This case report highlights Charles Bonnet Syndrome as a precursor to the development of major neurocognitive disorder due to Alzheimer’s disease in the elderly with visual impairment and the possible differential diagnoses that could be considered. We report a case of an elderly lady with no known previous medical illness, who presented for the first time to the psychiatric clinic with complex visual hallucinations consisting of well-formed images of people and inanimate objects of long standing duration of 18 months. About a year later, there was emergence of cognitive impairment which progressed gradually accompanied by other psychotic symptoms such as auditory hallucinations and persecutory delusions. There were no affective or obsessional symptoms. She had poor insight towards her illness. Ophthalmological examination revealed significant reduction in bilateral visual acuity. Otherwise, physical examination was unremarkable. She received inpatient treatment with Rivastigmine patch 4.6 mg/24 hours and Zydis 10 mg noctre. Her cognitive impairment and psychotic symptoms gradually improved over a period of 2 weeks upon commencing treatment and on subsequent follow-ups at outpatient clinic. She had also gained some insight into her illness. Charles Bonnet syndrome could be a possible precipitating factor and precursor to the development of major neurocognitive disorder due to Alzheimer’s disease in the elderly with visual impairment which is often overlooked or misdiagnosed and hence under reported.